España y el imperio de Maximiliano : finanzas, diplomacia, cultura e inmigración - Lida, Clara E. (Clara Eugenia) (Book collections on Project MUSE., 1999)
"Thorough study of Spain's role in Mexican affairs during the 1860s, with excellent essays on the debt, diplomacy, the Spanish view of Mexican culture as seen in France, and the identity of the Spanish community in Mexico. Also includes collection of short biographies of the leading players. Excellent contribution"--Handbook of Latin American Studies, v. 58.